Molecular survey of Hepatozoon spp. and piroplasmids in rodents and marsupials from midwestern Brazil, with evidence of a novel Piroplasmida clade (“South American Rodentia”) in the echimyid rodent Thrichomys pachyurus - dos Anjos Pacheco, Thábata (2025)
The order Piroplasmida (e.g., Babesia, Theileria, Cytauxzoon, and Rangelia) and suborder Adelorina (e.g., Hepatozoon) comprise protozoa of the phylum Apicomplexa, which are related to significant economic, veterinary, and medical concerns. This study aimed to investigate the molecular occurrence and evaluate the phylogenetic placement of the Hepatozoon and Piroplasmida agents in small mammals (rodents and marsupials) in midwestern Brazil. The maximum likelihood phylogenetic inference positioned the 18S ribosomal RNA (18S rRNA) sequences of Hepatozoon obtained from Hylaeamys megacephalus with those previously detected in Didelphis aurita from Brazil; however, the sequences of Hepatozoon retrieved from Nectomys rattus and Neacomys amoenus clustered in a sub-clade sister to a clade of sequences detected in small rodents from Brazil. Phylogenetic inference positioned the piroplasmid 18S rRNA sequences detected in Thrichomys pachyurus in a single sub-clade sister to a clade containing sequences previously detected in the Phyllostomidae bat Phyllostomus discolor from midwestern Brazil. In contrast, the piroplasmid cytochrome b mitochondrial gene (cytB) sequences obtained from T. pachyurus clustered into a single clade. In conclusion, a new host record is provided for Hepatozoon spp. from the rodent N. amoenus. Furthermore, this study expanded the Piroplasmida order diversity by identifying novel genotypes in T. pachyurus rodents, which were genetically related to the piroplasmid clade found in Neotropical bats and named herein the “South American Rodentia group.”